Wnt10b-overexpressing umbilical cord mesenchymal stem cells promote fracture healing via accelerated cartilage callus to bone remodeling. Issue 4 (1st April 2022) - Hu, Yuxiang; He, Yu; Fang, Jiarui; Liu, Yunlu; Cao, Yulin; Tong, Wei; Chen, Wei; Shao, Zengwu; Liu, Yong; Tian, Hongtao
ABSTRACT: The aim of this study was to investigate whether HUCMSCs Wnt10b could promote long bone fracture healing. Commercially-available HUCMSCs Emp (human umbilical cord mesenchymal stem cells transfected with empty vector) in hydrogel, HUCMSCs Wnt10b in hydrogel and HUCMSCs Wnt10b with the Wnt signaling pathway inhibitor IWR-1 were transplanted into the fracture site in a rat model of femoral fracture. We found that transplantation of HUCMSCs Wnt10b significantly accelerated bone healing in a rat model of femoral fracture. Meanwhile, three-point bending test proved that the mechanical properties of the bone at the fracture site in the HUCMSC Wnt10b treatment group were significantly better than those of the other treatment groups. To understand the cellular mechanism, we explored the viability of periosteal stem cells (PSCs), as they contribute the greatest number of osteoblast lineage cells to the callus. In line with in vivo data, we found that conditioned medium from HUCMSCs Wnt10b enhanced the migration and osteogenic differentiation of PSCs. Furthermore, conditioned medium from HUCMSCs Wnt10b also induced endothelial cells to form capillary-like structures in a tube formation assay, which was blocked by SU5416, an angiogenesis inhibitor, suggesting that enhanced vessel formation and growth also contribute to accelerated hard callus formation. In summary, our study demonstrates that HUCMSCs Wnt10b promote fracture healing via accelerated hard callus formation, possibly due to enhanced osteogenic differentiation of PSCs and vessel growth. Therefore, HUCMSCs Wnt10b may be a promising treatment for long bone fractures. Grapical abstract: uf0001